ANTIBACTERIAL ACTIVITY TEST OF BANANA PEEL ESSENTIAL OIL AGAINST ESCHERICHIA COLI (E. COLI) BACTERIA IN BIOCHEMISTRY LABORATORYUM - Diah kartika sari (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
A study on the antibacterial activity of essential oil from banana peel was conducted. The research was conducted in a span of two months starting from sample collection, sample distillation process, and testing the antibacterial activity of essential oil. This study was conducted to determine the antibacterial activity of banana peel essential oil as a natural antibacterial against Escherichia coli (E. coli) bacteria considering the resistance of synthetic antibacterials to pathogenic bacteria. Isolation of essential oil in banana peel using steam distillation method and antibacterial activity test using disc paper method. The distilled essential oil was purified using anhydrous sodium sulphate (Na2SO4) to separate the oil from water and other impurities without affecting the purity of the essential oil. The results of the antibacterial activity test of banana peel essential oil against Escherichia coli (E. coli) bacteria with a concentration of 50% obtained an inhibition zone of 10.5 mm and at a concentration of 25% of 9.1 mm including the medium category. More than 50% of banana peel essential oil is thought to be more effective because at that concentration level, antibacterial compounds that have potential as antibacterial agents have reached sufficient levels.